2021
DOI: 10.1001/jamaneurol.2021.2979
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthesia vs Local Anesthesia in Microelectrode Recording–Guided Deep-Brain Stimulation for Parkinson Disease

Abstract: IMPORTANCE It is unknown if there is a difference in outcome in asleep vs awake deep brain stimulation (DBS) of the subthalamic nucleus for advanced Parkinson disease. OBJECTIVE To determine the difference in adverse effects concerning cognition, mood, and behavior between awake and asleep DBS favoring the asleep arm of the study. DESIGN, SETTING, AND PARTICIPANTS This study was a single-center prospective randomized open-label blinded end point clinical trial. A total of 187 persons with Parkinson disease wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…In addition, as imaging and atlas techniques have improved, the role of MER has been called into question ( 39 ). At least one retrospective study has demonstrated no significant differences in mood between asleep and awake DBS cases, ( 44 ) but further work with larger, prospective studies are needed to truly compare the benefits of asleep vs. awake cases. Although there is some evidence that advances in interventional MRI technology has led to more accuracy regarding the anatomic placement of the DBS leads, the clinical outcomes between image-guided DBS and MER-guided DBS are similar ( 45 , 46 ).…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…In addition, as imaging and atlas techniques have improved, the role of MER has been called into question ( 39 ). At least one retrospective study has demonstrated no significant differences in mood between asleep and awake DBS cases, ( 44 ) but further work with larger, prospective studies are needed to truly compare the benefits of asleep vs. awake cases. Although there is some evidence that advances in interventional MRI technology has led to more accuracy regarding the anatomic placement of the DBS leads, the clinical outcomes between image-guided DBS and MER-guided DBS are similar ( 45 , 46 ).…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…Awake DBS is typically more time consuming, more expensive, and more taxing for both the patient and the surgical team, and many centers have transitioned to asleep DBS implantation with image guidance only. While multiple studies have been published suggesting that asleep DBS outcomes are comparable to those achieved with awake DBS [59][60][61], we remain convinced that using our surgical methodology, awake DBS with intra-operative physiology and patient feedback is safer, and results in better DBS outcomes for our patients. Particularly in the treatment of tremor disorders, where intra-operative tremor suppression correlates well with post-operative tremor suppression and intra-operative adjustments can readily be made to maximize tremor suppression and minimize adverse effects of stimulation, we believe outcomes of awake DBS should be superior to those of asleep DBS, where such intraoperative evaluations and adjustments are not possible.…”
Section: Awake Patients -Head Frame Applicationmentioning
confidence: 87%
“…5 Holewijin et al have conducted a single-center prospective randomized open-label blinded end-point clinical trial on 110 Parkinson patients undergoing DBS. 6 The patients were randomized to GA or LA with no sedation. Their primary outcome was a composite score of cognitive, mood, and behavior adverse events at 6 months.…”
Section: Introductionmentioning
confidence: 99%